Distress and resilience associated with workload of medical students. (4th May 2019) - Kiziela, Antanas; Viliūnienė, Rima; Friborg, Oddgeir; Navickas, Alvydas
Abstract: Background: University students face numerous stressors during their study curricula, which require adequate resilience to ensure healthy adaptation. Aims: To examine how relationships between study workload and mental health problems are moderated by resilience. Secondly, to compare our findings with other studies and assess differences in resilience and distress between medical and non-medical students. Methods: A prospective quantitative design was used. Participants completed a questionnaire package assessing resilience resources (Resilience Scale for Adults) and mental health (Core-OM: Clinical outcomes in routine evaluation – outcome measure) under three different conditions: heavy, low or regular workload. Results: During heavy workload, significantly higher distress score was found among medical students compared to other students (1.46 vs. 1.25; p < 0.05). Medical students had slightly higher overall resilience scores (5.21 vs. 4.94; p > 0.05). During heavy workload up to 20% of the participants had higher distress score than clinical samples' average from other studies. RSA score and Core-OM scores were inversely dependent ( p < 0.0001; r = −0.434). Conclusion: Findings suggest that distress mediated by heavy workload does not significantly affect resilience. Many students, especially medical, are experiencing high levels of distress. Resilience is associated with the decrease in distress.